Home buying kit for dummies - Tyson, Eric (Eric Kevin).; Brown, Ray (Raymond).; Tyson, Eric (Eric Kevin) (Hoboken, N.J. : Wiley, 2012)
Understand today's home buying market and make the best deal with this time-tested guide. Discover how to find the right property, make smart financial decisions, and understand the latest lending requirements and tax implications.
Introduction -- Home economics -- Financing 101 -- Property, players, and prices -- Making the deal -- The part of tens.
Includes index.
Rev. ed. of: Home buying for dummies. 4th ed. c2009.
System requirements: PC running Microsoft Windows or Macintosh running Apple OS X or later ; Microsoft Word and Excel ; Adobe Acrobat ; CD-ROM drive.
Keywords: House buying -- United States; Mortgage loans -- United States; Residential real estate -- Purchasing